Continuously Tunable and Highly Stable Random Lasers Based on CNCs-Doped Hydrogels - Zhiyu Wang; Guosheng Zhang; Zhijia Hu; Benli Yu; Sheng Zhou (Photonic Sensors)
Abstract This paper proposes a continuously tunable random lasers (RLs) based on the gain system of cellulose nanocrystals (CNCs)-doped hydrogels and the laser dye made of Rhodamine B (Rh B). Between them, the prepared CNCs-doped hydrogels have not only a weak scattering structure that can provide excellent multiple scattering, thus yielding a large gain, but also good mechanical properties that can provide great advantages in the tuning of RL. The experimental results indicate that the RL emission wavelength blue shifts with an increase in the stretching length. The continuous tuning range reaches up to 7.1 nm when the CNCs-doped hydrogels are stretched to 400%. In addition, the proposed CNCs-doped hydrogels effectively solve the problem of the structures of traditional hydrogels, which are easily destroyed during repeated stretching and ensure good stability of RL output and tuning. The RL error is tested and found to be less than 0.5 nm, when the same length is stretched during repeated stretching. Our results provide a new approach to obtain tunable and stable RLs. Simultaneously, in combination with the good biocompatibility of CNCs-doped hydrogels, the proposed RLs demonstrated great importance in the biological field.